Brain and behavioral correlates of action semantic deficits in autism - Moseley, Rachel L.; Mohr, Bettina; Lombardo, Michael V.; Baron-Cohen, Simon; Hauk, Olaf; Pulvermuller, Friedemann (Frontiers in Human Neuroscience, 2013)
Action-perception circuits comprising neurons in the motor system have been proposed as main building blocks of higher cognition; accordingly, motor dysfunction should entail cognitive deficits. Autism spectrum conditions (ASC) are marked by motor impairments but the implications of such motor dysfunction for higher cognition remain unclear. We here used word reading and semantic judgement tasks to interrogate action-related motor cognition and its corresponding fMRI brain activation in high-functioning adults with ASC. These participants exhibited hypoactivity of motor cortex in language processing relative to typically developing (TD) controls. Crucially, we also found a deficit in semantic processing of action-related words, which, intriguingly, significantly correlated with their underactivation of motor cortex to these items. Furthermore, the word-induced hypoactivity in the motor system also predicted the severity of ASC as expressed by the number of autistic symptoms measured by the Autism-Spectrum Quotient (Baron-Cohen et al, 2001). These significant correlations between word-induced activation of the motor system and a newly discovered semantic deficit in a condition known to be characterised by motor impairments, along with the correlation of such activation with general autistic traits confirm critical predictions of causal theories explaining cognitive and semantic deficits in ASC, in part, to dysfunctional action-perception circuits and resultant reduction of motor system activation.